2019
DOI: 10.1080/10749357.2019.1591038
|View full text |Cite
|
Sign up to set email alerts
|

Relationships between gait variability and ambulatory activity post stroke

Abstract: Background: Fall risk and balance confidence are related to gait variability and ambulatory activity post-stroke, yet whether a relationship exists between gait variability and ambulatory activity is unknown. Knowing if gait variability measured under naturalistic conditions is related to ambulatory activity could explain more about the relationship between falls and walking activity post-stroke. Objectives: To examine relationships between spontaneous, daily ambulatory activity and gait variability during sin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
7
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 30 publications
1
7
0
Order By: Relevance
“…The stroke group showed greater stride length variability and stride time variability suggesting heightened inconsistency in timing and distance between consecutive strides. These findings are in line with previous reports showing increased gait variability in spatial and temporal domains following stroke 11 , 41 . We found that both stride length variability and stride time variability were positively correlated to PCI in the stroke group (Table 2 ).…”
Section: Discussionsupporting
confidence: 93%
“…The stroke group showed greater stride length variability and stride time variability suggesting heightened inconsistency in timing and distance between consecutive strides. These findings are in line with previous reports showing increased gait variability in spatial and temporal domains following stroke 11 , 41 . We found that both stride length variability and stride time variability were positively correlated to PCI in the stroke group (Table 2 ).…”
Section: Discussionsupporting
confidence: 93%
“…Thus, it is currently difficult to estimate the impact of performing two tasks simultaneously on daily activities in stroke survivors. To improve the ecological validity of assessments, recent studies have explored DT abilities of stroke survivors in a real-life environment ( 19 , 20 ). Assessing DT abilities with a standardized and reproducible protocol in the community remains a challenge.…”
Section: Introductionmentioning
confidence: 99%
“…That is, regardless of how far they can walk during the 6 minute walk test, individuals who slow down during the test walk less in the community than more endurant individuals. Beyond long-distance walking speed, real-world community walking activity is also associated with step-to-step variability in the spatiotemporal determinants of walking speed (i.e., stride length and stride time); individuals with higher gait variability have lower balance confidence, increased fall rates, and less physical activity [5][6][7][8][9].…”
Section: Introductionmentioning
confidence: 99%